2021
DOI: 10.1177/21582440211006714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Social Apps on Consumer’s Purchase Attitude: Role of Trust and Technological Factors in Developing Nations

Abstract: This study investigates the impact of mobile social apps (MSAPs) on consumers’ online purchase attitude (COPA) with the mediating effect of trust (TRF) and technological factors (TF) drawing on IS theory—technology acceptance model—from the context of China. The article is compiled based on 600 responses obtained from online shoppers and analyzed using structural equation modeling. The study confirmed that MSAPs—Wechat, Weibo, and Virtual community apps—are positively correlated with consumers’ online purchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Notably, WeChat is a more prominent and highly useable application in mainland of China (Gan & Li, 2018; Liu et al, 2019). Several experts used WeChat for academic data collection over the past decades since we too inspired by such studies (Gan & Li, 2018; Liu et al, 2019; Waheed et al, 2021; Waheed & Zhang, 2020). This study is quantitative where experts advocated a higher significance of quantitative approach for study analysis (Han, Yan, & Piroozfar, 2022; Whatley, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, WeChat is a more prominent and highly useable application in mainland of China (Gan & Li, 2018; Liu et al, 2019). Several experts used WeChat for academic data collection over the past decades since we too inspired by such studies (Gan & Li, 2018; Liu et al, 2019; Waheed et al, 2021; Waheed & Zhang, 2020). This study is quantitative where experts advocated a higher significance of quantitative approach for study analysis (Han, Yan, & Piroozfar, 2022; Whatley, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that consumers' trust in the brand is an essential factor influencing consumers' attitude toward perceived brands, and the higher the consumers' trust the higher their attitude will be [27]. Waheed et al investigated the impact of mobile social apps (MSAPs) on consumers' purchase attitude (COPY) based on IS theory and technology acceptance modelling and found that there is a significant positive effect of consumers' trust on their purchasing attitude [28]. Lee, while exploring real estate intermediary loyalty using linear structural equation modelling, found that there was a significant positive effect of consumers' trust on attitude with the largest path coefficient [29].…”
Section: Consumers' Trust and Consumers' Attitudementioning
confidence: 99%
“…The competition in the online retail market gets more intensified due to the global COVID-19 epidemic ( Yi et al, 2022 ). New technologies represented by the Internet, new media, cloud technology, and big data have become new driving forces for the development of media companies ( Waheed et al, 2021 ; Yi et al, 2021 ), and non-contact consumption will gradually become the main consumption pattern in the post-epidemic era. Non-contact consumption makes consumers unable to truly touch products online before purchase, thus, lacking sensory experience ( Yoo and Kim, 2014 ) and triggering great uncertainty about their purchase intention and behavior ( Rathee and Rajain, 2019 ).…”
Section: Introductionmentioning
confidence: 99%